PENGARUH KEPUTUSAN INVESTASI, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Arista Sri Ayu Lestari; suhardi suhardi (JEM Jurnal Ekonomi dan Manajemen, 2020)
The company's main goal is to increase the prosperity of owners and shareholders and to maximize the value of the company. Company value is the main focus in order to attract potential investors to invest, the company expects that financial managers can do the best for the company by maximizing the value of the company so that the welfare of shareholders can be achieved. This study aims to determine the effect of investment decisions, company size, and profitability on firm value in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2014-2017. The sampling technique in this study was the purposive sampling technique. The sample in this study were 10 companies in a period of 4 years. The analysis technique used in this study is panel data regression analysis using Eviews software. The results showed that investment decisions had a positive effect on firm value, company size had no effect on firm value, and profitability had a positive effect on firm value. Future research is recommended to add variables or conduct research in other industries and use different methods.